Glennon Brothers: Old Dogs Need to Learn New Tricks. (May 2017) - Clinton, Eric; Faherty, Catherine M.; Diaz–Moriana, Vanessa; Craig, Justin B.
This case study presents the story of Glennon Brothers, a third–generation family–owned sawmilling business in Ireland. As the firm evolved through the organizational life cycle and the complexity of firm operations increased, a different style of management was required to navigate the family business to the next stage. The brothers needed to move from being managers to managing managers. This case study highlights how coleaders can become comfortable with each other and unintentionally overlook the need to change their managerial priorities in line with the business's evolution.